THE USE OF AMINO ACIDS FOR CORRECTION IN CHRONIC ALCOHOL INTOXICATION - Kamolov Khushnud Yoqubovich (Zeta Repository, 2023)
The liver is a very resilient organ with unique regeneration abilities. Even if there are very few healthy cells left in it, the liver will continue to perform its functions.However, alcohol can completely destroy this organ in just a few years.Drinking alcohol leads to alcoholic liver disease (ALD), which ends in cirrhosis of the liver and death.